The English Advantage - Flamm, Jacqueline (New York Newbury House Publishers, 1991)
The English Advantage uses an innovative combination of authentic language, diverse vignettes, and a variety of interactive activities to teach foreign language students-studying either in The United States or abroad-to use English naturally and purposefully.
Keywords: English Practice